A Review of Research and Writing Textbook - Mohammad Armand (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Textbooks are one of the most important teaching tools. Therefore, it is necessary to be very careful about how they are designed and edited. Works on textbook design and authoring have been published, one of which is textbook research and writing that can be used by scholars, authors, and textbook contributors. In this article, this book has been criticized, using a critical philosophical research. The importance of this book in reflecting the wide range of textbook research in the world, its being research-oriented, and addressing fundamental issues are among the advantages.  The benefits of this book include the use of various tools to understand more about the contents, such as charts and tables, and the type of letters and their size. Its disadvantages include failure to rationalize the content and misinterpretation of some concepts, lack of proper design and contrast of colors, and inappropriate margins and unattractiveness.